Visual inspection results and evaluation of Akhtala tailing safety based on tailing management facility safety methodology; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 335, № 2 - Sahakyan K. Kristine (2024, 2024)
Relevance. Mining sector is one of the leading branches of the industry in Armenia. Therefore, effective government regulation of the sector based on a sound legal basis is a necessity. Accidents at tailing management facilities are posing a high risk to people and environment especially in their near vicinity and often have a transboundary impact. The tailing management facility safety methodology elaborated under the auspices of the German Environmental Agency is an efficient tool for quick assessment of the technical condition of the tailing management facilities. Aim. To present the results of application of the tailing management facility methodology in Armenia, which was applied to the operated Nahatak tailing management facility of the Akhtala Ore Dressing Combine (Lori region, Armenia). Objects. Tailing management facility methodology was applied to the operated tailing management facility Nahatak of the Akhtala Ore Dressing Combine, for which all documentation was checked. Enrichment wastes were stored at the tailing management facility during processing copper ore from the Shamlug mine and polymetals from the Akhtala mine. The main visual inspection was carried out in three parts of the tailing management facility: main dam, drainage canal and secondary dam. Special attention was drawn to the main dam conditions. The video recorded by a drone was used to explore the dam bottom-line. Methods. The tailing management facility methodology includes the following elements: the method of evaluation of Tailings Hazard Index; the tailing management facility checklists including the questionnaire for visual and documentation inspection, the evaluation matrix for the tailing management facility safety level; the measures catalogue for taking actions to improve tailing management facility safety. The questions of each tailing management facility checklist are stated in a way to encompass the minimum set of the requirements, critical for tailing management facility safety, which allows evaluating the tailing management facility conditions. Questions in all groups of the checklist are sorted by the tailing management facility lifecycle and each subsection contains relevant questions applied to a specific stage (design, construction, operation, re-cultivation, closure). Application of the tailing management facility checklist is supported by a measures catalogue with short-, mediumand long-term safety measures. Results. The tailing management facility methodology was used/tested for the operated tailing management facility in Armenia for the first time. Тhe main problems of the Nahatak tailing management facility were identified and analyzed, and appropriate recommendations were provided based on them. Based on the obtained results it can be concluded that the main problems are related to the drainage system and the management of water flows, some parts of the primary dam that require restoration, as well as the improvement of monitoring systems. At the same time the experience of application of the tailing management facility methodology in Armenia, allowed improving this methodology and making it the most effective working tool for quick and efficient visual inspection of tailing management facilities and for thorough inspection of relevant documentations. The user-friendly tailing management facility safety methodology (with questionnaires of visual and documentation checking) is an efficient tool for quick assessment of the technical condition of the tailing management facilities, as well as for training staff both in the governance bodies and in mining enterprises.